STRATEGI PENGEMBANGAN DESTINASI WISATA DESA BONGO, KABUPATEN GORONTALO - Ramang Husin Demolingo (JURNAL MASTER PARIWISATA, 2015)
This study analyzes the development strategy of Bongo Village, Gorontalo District, Sulawesi, as a tourism destination. This village has a great potential of natural and cultural resources but it has not fully developed yet as tourist attractions.The study starts by identifying tourism potential of the village and followed by setting up the strategy to develop the village as a attractive tourism destination. This study used qualitative descriptive data analysis and SWOT analysis. The result shows that tourism potentials of the Bongo village includes natural tourism resources, artificial resources, cultural and social economic potential, accessibility and supporting facilities, which have not been used and managed well. In addition, some public facilities and infrastructure are inadequate. This study suggests that there is a need for the government involvement in establishing an institution of tourism management, improving the quality of human resources, building infrastructure of tourist facilities which are still lacking, as well as forming a close cooperation between tourism stakeholders including the community.